Literature reviews: McKinsey 7S model to support organizational performance - Suwanda, Suwanda; Nugroho, Bernardus Yuliarto (Technium Social Sciences Journal, 2022)
This paper aims to describe how performance measurement in public and private organizations using the McKinsey Model 7S analysis method (Strategy, Structure, System, Shared value, Skill, and Staff). The research method used is a qualitative research method with a literature review approach. The source of the research data used is a journal article of research results in public and private organizations that uses McKinsey's Model 7S analysis to measure the performance of the organization. The results of studies in several previous studies state that internal organizational factors according to 7S McKinsey such as S trategy, Structure, System, Shared value, Skill, and Staff are very influencing each other which has an impact on the performance of an organization.